Lanthanide-Based Langmuir–Blodgett Multilayers: Multi-Emissive, Temperature-Dependent Thin Films - O’Neil AT; Kitchen JA (MDPI (Basel, Switzerland), 2022)
Multi-emissive compounds have attracted significant attention from the research community owing to the wide array of potential application areas. However, to move towards application, such systems should be readily immobilized by solution-based methods to form soft materials such as gels and films. Herein we report the use of Langmuir–Blodgett (LB) deposition to easily immobilize luminescent lanthanide-based amphiphilic solids into multi-emissive ultrathin LB films, by multilayering different luminescent amphiphiles. Utilizing this technique, we have reliably fabricated dual- and triple-emissive films where the overall emission from the film is tuned. Furthermore, we have demonstrated that these multi-emissive films are temperature-dependent, with emission profiles significantly altering from 294 to 340 K, resulting in colour changes and potential application as ultrathin, contactless ratiometric thermometer coatings.
Keywords: lanthanides; supramolecular materials; Langmuir–Blodgett films; multi-emissive materials; colour-tunable materials; temperature sensors; ratiometric thermometer